PENINGKATAN BERAT BADAN ANAK MELALUI PENYELENGGARAAN MAKANAN GIZI SEIMBANG DENGAN KEGIATAN FUN COOKING - HANDINI, MYRNAWATI CRIE (PPs UNJ, 2012)
The Objectives of the research are (1) to create an event of fun cooking that cook nutrient food (quality) and (2) to increase the children body weight through the use of nutrient food during the fun cooking activity that run from Monday to Thursday on September and October (quantitative).The research is being done in TK (plau group) Kemala Bhayangkari 17 Cipinang Bawah, East Jakarta with a population of 20 children that consist of 12 girls and 8 boys. Action research metgod is being used on the research that uses Kemmis and Mc Taggart design.The result show that weight increment is happening within the children, even though the increase of two children weight is less than one kilogram. The research is done on one cycle only as the result is satisfying all the success criteria that have been appointed with the collaborator.Keywords: children weight, nutrient food